Assessing health professional education : workshop summary - Cuff, Patricia A. (Online access: NCBI NCBI Bookshelf., 2014)
"Assessing Health Professional Education is the summary of a workshop hosted by the Institute of Medicine's Global Forum on Innovation in Health Professional Education to explore assessment of health professional education. At the event, Forum members shared personal experiences and learned from patients, students, educators, and practicing health care and prevention professionals about the role each could play in assessing the knowledge, skills, and attitudes of all learners and educators across the education to practice continuum. The workshop focused on assessing both individuals as well as team performance. This report discusses assessment challenges and opportunities for interprofessional education, team-based care, and other forms of health professional collaborations that emphasize the health and social needs of communities"--Publisher's description